P454 Evaluation of the nutritional care status in italian centers managing patients affected by inflammatory bowel disease. (21st January 2022) - Saibeni, S; Bezzio, C; Armuzzi, A; Daperno, M; Zanetti, M; Vernero, M; Giorgetti, G M
Abstract: Background: Patients affected by IBD are at risk for malnutrition. An impaired nutritional status is associated with several negative outcomes (increased risk of flares, poor response to therapy, hospitalizations, surgical interventions, and post-surgical complications). Nutritional care is defined as "the form of nutrition, nutrient delivery and the system of education that is required for meal service or to treat any nutrition-related condition in both preventive nutrition and clinical nutrition". The aim of this study was to assess the current status of the nutritional care in the Italian Centers managing IBD patients. Methods: A dedicated web-based questionnaire developed by the Italian Society of Artificial Nutrition and Metabolism (SINPE) was sent to all the 120 IBD Centers referring to IG-IBD. The relevance of the nutritional care was assessed using a Visual Analogue Scale from 0 (the less) to 100 mm (the most) and expressed as mean ± SD. Results: 63.3 (%) questionnaires were returned. The presence of an IBD-dedicated nutritionist is present in 27/120 (35.5%) Centers, while in 25/120 (32.9%) the evaluation of the nutritional status is considered hard to obtain. In 52 (68.4%) of Centers is present an IBD multidisciplinary team, in 22 of these (42.3%) a nutritionist is included. In the outpatient setting, the malnutrition risk is evaluated at each visit in 28 (36.8%) Centers, in case of active or complicated disease in 29 (38.2%) and only when the presence of malnutrition is suspected in 34 (44.7%). The nutritional status is evaluated at each visit in 28 (36.8%) Centers, in case of active or complicated disease in 38 (50.0%), while only when the presence of malnutrition is suspected in 31 (40.8%). In 67 (88.2%) Centers the evaluation of nutritional parameters is directly assessed by the gastroenterologist, by means of blood chemistry (98.7%), antropometric indices (82.9%) and impedenziometry (14.5%). For hospitalized IBD patients, the malnutrition risk and the nutritional status are evaluated at each admission in 37 (48.7%) and 42 (56.0%) Centers and only when the presence of malnutrition is suspected in 39 (51.3%) and in 37 (48.7%). The relevance of nutritional assistance in clinical management of IBD patients and in the institutional diagnostic and therapeutic paths were considered high by physicians: 86.5 ± 12.2 mm and 86.7 ± 13.1 mm, respectively. Conclusion: Nutritional care for IBD patients appears quite far from being satisfactory in the Italian reality and at the same time highly wanted. Educational and logistic interventions are needed to improve the assessment and the treatment of malnutrition in the everyday clinic practice.